Social Capital Value in Tahlilan and Yasinan Tradition - Tanjung, Hasan Basri; Mujahidin, Endin; Sadiyah, Maemunah; Wibowo, Rimun; Bahagia, Bahagia (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Tahlilan and Yasinan are part of religious activities so they are very beneficial for social life. The research will find social values contained in tahlilan and yasinan activities including social capital. While the research method used is a qualitative research method. This method intends to do a detailed description of the findings of each variable in tahlilan and yasinan activities. While the research results will be analyzed using a triangulation approach, namely an analysis that combines various data collection methods so that results and conclusions are obtained. The results of this study indicate that tahlilan and yasinan contain social value because tahlilan includes social care where neighbors have a social responsibility to families who are grieving, such as family members who have died. At the same time strengthens social cohesion because each individual will gather where so far they have their own activities. In fact, it includes acts of alms because these activities provide food and drink for everyone present at the tahlilan and yasinan events. Finally, there is the value of gotong royong because neighbors participate hand in hand to take care of the funeral process. Mutual cooperation activities began to help prepare the needs of yasinan and tahlilan.